RETRACTED: microRNA-155 Modulates Hepatic Stellate Cell Proliferation, Apoptosis, and Cell Cycle Progression in Rats With Alcoholic Hepatitis via the MAPK Signaling Pathway Through Targeting SOCS1 - Liu, Dengtao; Han, Ping; Gao, Chunhai; Gao, Wei; Yao, Xiaocui; Liu, Shulan (Frontiers in Pharmacology, 2020)
The aim of this study was to investigate the regulatory function of the non-coding microRNA-155 (miR-155) and suppressor of cytokine signaling 1 (SOCS1) in alcoholic hepatitis (AH) and its potential mechanism associated with mitogen activated protein kinase (MAPK) signaling pathway. Levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (ALB), total bilirubin (TBIL), malondialdehyde (MDA), and superoxide dismutase (SOD) were measured in a rat mode of AH. .The biological prediction website (microRNA.org) and dual luciferase reporter gene assay were used to identify whether SOCS1 was a direct target of miR-155, and effects of miR-155 and SOCS1 on cell viability, cycle progression and apoptosis of hepatic stellate cells were assessed using RT-qPCR, Western blot assay, MTT assay, Annexin V/PI double staining and PI single staining. The levels of ALT, AST, MDA and TBIL and the liver cell morphology in AH model rats were all prominently changed. miR-155 suppressed SOCS1 by specifically binding to SOCS1-3’-UTR to activate the MAPK signaling pathway. SOCS1 had low expression while miR-155 was highly expressed in AH rats. miR-155 promoted hepatic stellate cell viability and cycle progression, and reduced cell apoptosis by silencing SOCS1. Together, we find that silenced miR-155 could up-regulate SOCS1 and inactivate MAPK signaling pathway, thereby inhibiting the proliferation of alcoholic hepatic stellate cells and promoting cell apoptosis.